Mutation analysis of the cathepsin C gene in Indian families with Papillon-Lefèvre syndrome - Srivastava Satish; Sethuraman Gomathy; Sathyan Parthasarathy; Prasad Pullabatla; Markandaya Manjunath; Selvaraju Veeriah; Thakker Nalin; Kumar Arun (BMC, 2003)
Abstract Background PLS is a rare autosomal recessive disorder characterized by early onset periodontopathia and palmar plantar keratosis. PLS is caused by mutations in the cathepsin C (CTSC) gene. Dipeptidyl-peptidase I encoded by the CTSC gene removes dipeptides from the amino-terminus of protein substrates and mainly plays an immune and inflammatory role. Several mutations have been reported in this gene in patients from several ethnic groups. We report here mutation analysis of the CTSC gene in three Indian families with PLS. Methods Peripheral blood samples were obtained from individuals belonging to three Indian families with PLS for genomic DNA isolation. Exon-specific intronic primers were used to amplify DNA samples from individuals. PCR products were subsequently sequenced to detect mutations. PCR-SCCP and ASOH analyses were used to determine if mutations were present in normal control individuals. Results All patients from three families had a classic PLS phenotype, which included palmoplantar keratosis and early-onset severe periodontitis. Sequence analysis of the CTSC gene showed three novel nonsense mutations (viz., p.Q49X, p.Q69X and p.Y304X) in homozygous state in affected individuals from these Indian families. Conclusions This study reported three novel nonsense mutations in three Indian families. These novel nonsense mutations are predicted to produce truncated dipeptidyl-peptidase I causing PLS phenotype in these families. A review of the literature along with three novel mutations reported here showed that the total number of mutations in the CTSC gene described to date is 41 with 17 mutations being located in exon 7.